A Fresh Look at the Debate on the Causes of Poor Performance of Certain Irrigation Schemes: The Complexity of Hydraulic Behaviour of Canal Systems†. (17th May 2019) - Plusquellec, Hervé
Abstract: The paper starts with a retrospective review of the debate on the causes of poor performance of irrigation schemes in the 1990s which resulted in a sharp decline in the interest of financing agencies in the irrigation sector and a shift to a new model of irrigation projects focusing on participatory irrigation management associated with rehabilitation works. Evidence is overwhelming that many new‐type projects have had mixed results. It is evident that improved management alone cannot boost the performance of poorly designed irrigation systems. Design flaws should be corrected. This paper goes on to discuss the complexity of the hydraulics of irrigation canals and the intricate behaviour of a hierarchy of canal systems with innumerable numbers of nodes that should respond to changes in demand and supply. Minor differences at the head of main canals may result in serious deviations from the planned operation and even extreme differences in delivery or chaos at the tail ends. It was only in the mid‐1980s that hydraulic academics studied these phenomena of instability related to the sensitivity of control structures and their interaction. Admittedly occasional observers from other disciplines could not identify the technical causes of the poor performance of some irrigation schemes. © 2019 John Wiley & Sons, Ltd. Résume: L'article débute par une revue rétrospective du débat sur les causes de la mauvaise performance des projets d'irrigation au début des années 1990 qui a entrainé une forte baisse de l'intérêt des organismes de financement pour le secteur de l'irrigation et passer à un nouveau modèle de projets d'irrigation mettant l'accent sur la gestion participative de l'irrigation associée aux travaux de réhabilitation. Force est de reconnaitre une trentaine d'années plus tard que les projets de ce type n'ont pas obtenu les résultats espérés. Il est évident qu'améliorer la gestion seulement ne peut améliorer la performance de projets mal conçus. Les défauts de conception doivent être corrigés. Cet article présente ensuite la complexité de l'hydraulique des canaux d'irrigation et le comportement complexe de systèmes de canaux avec un nombre considérable de points de contrôle devant répondre à des variations de l'offre et de la demande en eau. Des déviations mineures en tête des réseaux d'irrigation peuvent produire des différences extrêmes de la fourniture en eau dans les zones situées à l'aval, voire même conduire au chaos. C'est seulement au milieu des années 1980 que les universitaires spécialisés en hydraulique ont étudié les phénomènes d'instabilité liés à la sensibilité des structures de contrôle et l'interaction entre ces structures. Il est clair que les observateurs occasionnels de systèmes d'irrigation ne pouvaient identifier ces causes techniques de la mauvaise performance de certains projets d'irrigation. © 2019 John Wiley & Sons, Ltd.